Tree HR as a Multilevel Heuristic Framework for Human Resource Management and Development in Islamic Educational Institutions: A Systematic Scoping Review - Tengku Ramly, Amir; Sinta Dewi, Reni; Lisnawati, Santi; Iba, Zainudin (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study aims to map evidence on HRM and HRD in Islamic educational institutions and to formulate a multilevel conceptual framework based on Tree HR to read the conceptual interconnections among values, competencies, character, institutional context, and educational outcomes. Design/methods/approach – The research used a systematic scoping review based on PRISMA-ScR. The search was conducted in Scopus, Web of Science, ERIC, and secondary searching for the period from 2010 to 2025. From 151 records, 4 duplicates were removed, 147 records were screened, 56 were excluded, and 91 studies were analyzed through charting, thematic synthesis, methodological characterization, and mapping to the Tree HR components. Findings – The findings show an increase in publications from 2023 to 2025, with a peak in 2025 of 38 studies or 41.8%. The highest thematic concentration was in Trunk, namely competencies and HRD, which appeared in 62 studies, as well as Fruits/Leaves, namely performance, service quality, and educational outcomes, in 61 studies. Roots appeared in 44 studies, whereas Personality/Character appeared in 34 studies. The main gaps include weak multilevel testing, heterogeneity of indicators, the dominance of non-causal designs, and limited instrument validity across contexts. Research implications – This framework can be used as an initial tool for reflection and diagnosis of human resources in madrasahs, pesantren, integrated Islamic schools, and Islamic Religious Higher Education Institutions (PTKI), particularly for training planning, performance assessment, career development, and the formulation of human resource policy indicators for Islamic education.